WATER RESOURCE MANAGEMENT AND ECONOMIC POLICY IN ARID REGIONS - Khare, Prof. Hemant (IJRDO - Journal of Social Science and Humanities Research, 2026)
Water resource management in arid regions poses a critical challenge for sustainable development due to the scarcity of freshwater, erratic rainfall patterns, high evapotranspiration rates, and increasing anthropogenic demands. These regions—characterized by minimal precipitation and limited surface water availability—face growing pressure from agriculture, urbanization, and industrialization. This paper examines the complex interplay between water resource management and economic policy in arid zones, with a focus on how strategic economic interventions can enhance water efficiency, ensure equitable access, and promote long-term economic resilience. Drawing upon global case studies from countries like India, Israel, and regions in North Africa, the study evaluates policy instruments such as water pricing, subsidies for micro-irrigation, investments in rainwater harvesting, and the promotion of wastewater reuse. It critically assesses the effectiveness of Integrated Water Resource Management (IWRM) and the importance of decentralized governance models in engaging local communities. The paper argues that without policy coherence and long-term vision, short-term economic incentives may aggravate water stress and environmental degradation. Furthermore, the study emphasizes the necessity of aligning economic policy with environmental sustainability to build climate-resilient economies in water-scarce areas. It concludes that adaptive, economically sound, and ecologically sensitive water management strategies are essential for addressing both current and future challenges in arid regions.